PENGEMBANGAN DESA WISATA AIR PANAS TIRTA ANGSANA DESA SUKAMULYA KECAMATAN PAKENJENG BERBASIS PARIWISATA BERKELANJUTAN DAN PEMBERDAYAAN MASYARAKAT - Ade Burhanudin; Aip Zaenal Mutaqin; Aceng Ulumuddin Ulumuddin; Yagus Yagus (The Indonesian Journal of Public Administration (IJPA), 2026)
Sukamulya Village in Pakenjeng District has natural tourism potential in the form of the Tirta Angsana hot springs, which can be developed as a nature-based and health-based tourist destination. This potential has the potential to boost the community's economy through planned and sustainable village tourism development. However, destination management still faces several obstacles, such as limited facilities, suboptimal management, and low community participation. The success of village tourism development is strongly influenced by community involvement and the application of sustainable tourism principles that consider environmental, social, and economic aspects (Sunaryo, 2013; UNWTO, 2018). This study aims to identify the tourism potential of Tirta Angsana Hot Springs and formulate a village tourism development strategy based on sustainable tourism and community empowerment. The study used qualitative methods with a descriptive approach through observation, interviews, and documentation. The results indicate that Tirta Angsana Hot Springs has significant tourism potential in terms of natural resources, environmental panoramas, and community economic opportunities. Tourism development requires improved facilities, strengthened community institutions, and collaboration between the government, tourism managers, and the local community (Yoeti, 2008).